Determinant Of Accounting Understanding - Sufiyati; Sofia Prima Dewi; Merry Susanti (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2020)
This study was made to determine the effect of perception of intellectual intelligence, emotional intelligence, spiritual intelligence, and learning behaviour on understanding accounting. The collection method was carried out by distributing questionnaires to Tarumanagara University students. The questionnaire was distributed from March to May 2019. Data processing methods were carried out using partial least square-structural equation modelling (PLS-SEM). The results showed that emotional intelligence and learning behaviour has no influence on students ' understanding of accounting. Perception of intellectual intelligence possessed by students only influence understanding Accounting Principle 1 and Accounting Principle 2. Emotional intelligence has no influence on understanding accounting. Spiritual intelligence possessed by students only influences on understanding of Accounting Principle 1. Learning behaviour has no influence on understanding accounting.